If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 86 + 2(3x + -12) = 0 Reorder the terms: 86 + 2(-12 + 3x) = 0 86 + (-12 * 2 + 3x * 2) = 0 86 + (-24 + 6x) = 0 Combine like terms: 86 + -24 = 62 62 + 6x = 0 Solving 62 + 6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-62' to each side of the equation. 62 + -62 + 6x = 0 + -62 Combine like terms: 62 + -62 = 0 0 + 6x = 0 + -62 6x = 0 + -62 Combine like terms: 0 + -62 = -62 6x = -62 Divide each side by '6'. x = -10.33333333 Simplifying x = -10.33333333
| 3(2x+1)x=-39 | | 8.3-(-2.1)= | | 5=q+12 | | 9x^3+6x^3+7= | | 120(5000-0.75x)= | | y=-16t^2+64t+8 | | .02y+.18=3 | | 0+4+4x= | | (3x-20)+(2x)=180 | | 6-9-d=3d | | 7.3+1.9y-(4.7x+5.8y)= | | Y=7*4x | | 1/2x+x= | | 0.21x-55=29 | | q^2-12q+20=0 | | -1x-5x=12 | | 2(3x+1)=15 | | 4m+6n-8+(8m-3)= | | -19=x-11 | | X=3-6*3+2 | | -4y-1=-17.25 | | x+1/2x+4+4x= | | q^2+3z-40=0 | | -x(5x+2)=0 | | 4n^3-2n= | | X=3p+27 | | 2x^2-1-10=0 | | 3[7-2(j-8)]=4j+2 | | -12x+2=2x-166 | | m+38=-44 | | 0.3x-8=25 | | x-4sqrt(x)-12=o |